Avaliação da viabilidade técnico-financeira da exploração de energia eólica em uma salina do Rio Grande do Norte - Pereira, Allan Viktor da Silva (Universidade Federal Rural do Semi-Árido, 2018)
The environmental impact generated by the exploitation of non-renewable energy sources, with emphasis on fossil fuels, as well as their forecast of depletion, has stimulated the search for alternative sources of energy, including wind energy. Less impactful than hydroelectric energy, and more efficient than solar energy, wind energy can be obtained in the most diverse locations on the planet, through a relatively simple production process, in which the movement of the masses of air is picked up by propellers Connected to generators (mechanical power), which in turn is converted into electricity. The objective of this work is to analyze the feasibility of the implantation of a wind farm in the municipality of Porto do Mangue/RN, for this was studied the technical feasibility of this implantation where the topography of the terrain was evaluated and the speed of the winds of the region, based on the data obtained in the INMET, the economic viability for the implementation of the wind farm was also studied, through a cash flow with all the revenue and expenditure of the wind undertaking requiring an initial investment of R$ 9,735,000.00. A 15% TMA was adopted and the VPL and TIR were calculated with the cash flow data that resulted in R$-4,346,988.91 and 1% respectively. The results presented by the analysed indicators implied in the refusal of the project, for presenting more than one negative criterion the implantation of the wind park.
Monografia
Keywords: Energia renovável; Custo beneficio; Aproveitamento eólico; Renewable energies; Cost benefit; Wind use; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA